2021
DOI: 10.1007/s12035-021-02567-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cellular Formation and In Vivo Seeding Effects of Hexameric β-Amyloid Assemblies

Abstract: The β-amyloid peptide (Aβ) is found as amyloid fibrils in senile plaques, a typical hallmark of Alzheimer’s disease (AD). However, intermediate soluble oligomers of Aβ are now recognized as initiators of the pathogenic cascade leading to AD. Studies using recombinant Aβ have shown that hexameric Aβ in particular acts as a critical nucleus for Aβ self-assembly. We recently isolated hexameric Aβ assemblies from a cellular model, and demonstrated their ability to enhance Aβ aggregation in vitro. Here, we report t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…In Perrin et al, we found that the dimeric orientation of C99 that favored the Aβ42 processing line and localized in intracellular compartments was more efficiently processed by PS2 [96]. In Vrancx et al, we reported that specific hexameric-like Aβ42 assemblies were majoritily produced by PS2 in vesicular compartments [115]. The fact that PS2 favors Aβ42 processing line in late endosomes must also be put in perspective with the observation that BACE1, the limiting enzyme of APP amyloidogenic processing, is predominantly found in endosomal compartments [116][117][118][119].…”
Section: App Dimeric Conformation Controls Its Intracellular Localiza...mentioning
confidence: 84%
See 1 more Smart Citation
“…In Perrin et al, we found that the dimeric orientation of C99 that favored the Aβ42 processing line and localized in intracellular compartments was more efficiently processed by PS2 [96]. In Vrancx et al, we reported that specific hexameric-like Aβ42 assemblies were majoritily produced by PS2 in vesicular compartments [115]. The fact that PS2 favors Aβ42 processing line in late endosomes must also be put in perspective with the observation that BACE1, the limiting enzyme of APP amyloidogenic processing, is predominantly found in endosomal compartments [116][117][118][119].…”
Section: App Dimeric Conformation Controls Its Intracellular Localiza...mentioning
confidence: 84%
“…As a consequence, a whole set of Aβ assemblies intermediate in Aβ fibril formation are present in the brain parenchyma. Some of them were shown to be readily formed in cells and having seeding properties when monomeric Aβ42 is available [115,158] Peculiar motifs present in the Aβ sequence largely contribute to its complex aggregation properties. Strikingly, TM interaction motifs appear to play a key role not only in Aβ dimerization but also in aggregation.…”
Section: Jm/tm Determinants Drive Aggregation Steps (Nucleation) Lead...mentioning
confidence: 99%
“…Neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease, and Huntington’s disease, are ascribed to pathogenic molecular processes involving conformational transitions of amyloidogenic proteins into toxic aggregates such as oligomers and fibrils ( 1-3 ). In addition to certain oligomers being deleterious aggregates ( 4, 5 ), amyloid fibrils have been demonstrated to exert cytotoxicity and play key roles in the persistence, progression, and propagation of amyloid diseases ( 6 ). Cross-β structures have been found in amyloid fibrils from various amyloidogenic proteins, suggesting that in-register parallel β-sheet formation is a universal feature of amyloid fibril structures ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…PD, EVs has been usually isolated from the conditioned medium of diverse neuronal cellular lines as SH-SY5Y(Emmanouilidou et al, 2010;Gustafsson et al, 2018;Lauritzen et al, 2019;Meng et al, 2020;Ozansoy et al, 2020;Park et al, 2020;Santa-Maria et al, 2012;Vrancx et al, 2021;Yuyama et al, 2019;Zarrin et al, 2021), N2a…”
mentioning
confidence: 99%
“…SH-SY5Y human neuroblastoma cell line has been widely employed to study both AD and PD. For AD, EVs isolated from SH-SY5Y expressing amyloid precursor protein (APP) Swedish or C99 (which is the β-secretase-derived APP C-terminal fragment (CTF)), were enriched in APP-CTFs and oligomeric CTFs(Lauritzen et al, 2019).Additionally, hexameric Aβo, were only found in EVs derived from SH-SY5Y, while monomeric Aβ was exclusive of the soluble proteins fraction of the culture media(Vrancx et al, 2021). Moreover, Raman spectroscopy analysis of EVs derived from MC65, a human neuroblastoma cell line over-expressing intracellular Aβ, revealed two intense Raman peaks that were attributed to Aβ incorporation in the EVs(Imanbekova et al, 2021).…”
mentioning
confidence: 99%